(3GdMce GdeMdj aj GdhWf GdYQHj hEJLGgGJ GdJWhjQ (B/s - (3GdWYGefI, eMeO eMehOs; (3YHO GdhgGH, SejQ eMeO s ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 2005)
(3GdMce GdeMdj (B((3EWGQ fXQj(B)- (3GdMce GdeMdj aj HdGO GdTGe(B- (3GdMce GdeMdj aj hGOj Gdfjd(B- (3GdMce GdeMdj aj THg LRjQI GdYQHjI(B- (3GdMce GdeMdj aj GdeZQH GdYQHj(B- (3GdEJLGgGJ GdeYGUQI aj GdMce GdeMdj(B- (3GdMce GdeMdj aj GdhWf GdYQHj(B- (3JMdjd ebGQf hQDjI eSJbHdjIs
Keywords: (3GdEOGQI GdeMdjIs; (3GdMce GdeMdjs; (3GdhWf GdYQHjs